Morphological Analysis of Derivational Prefixes in Fable Story of “Raja Lebah dan Sesendok Madu” - Lusi Susanti (Unipdu Jombang, 2020)
Abstract As we know that language is very important to our life to interaction in our daily life. The purpose of this study to describe the derivation prefixes which happen in the fabled story and will focus an analysis of the derivational prefixes in the fabled story “Raja Lebah dan Sesendok Madu”. This data research is a qualitative description, data collection using the literature study. Data analysis uses word-class classification in the speech section. The results of this study show that Derivational prefixes consist of se-, me-, meN-, ber-, di-. Although they are included in the derivation prefix they also have different in word classes. For example the word “sendok” as a noun and the word “sesendok” as an adverb. Based on the result from the analysis derivational prefixes above we find that there are several words that have different word classes when we add the prefix phonemes in front of a word. For example, the words